Neurodegenerative diseases and cancer: sharing common mechanisms in complex interactions - Natalia González Rojas, Martin Cesarini, José Luis Etcheverry, Gustavo Andrés Da Prat, Valeria Antico Arciuch, Emilia Mabel Gatto (Journal of Integrative Neuroscience, 2020)
Several epidemiological studies support low cancer rates in patients with neurodegenerative disorders, including Parkinson's disease, Huntington's disease, and Alzheimer's disease. Different mechanisms were raised as possible causes, from mutated tumor suppressor genes (PARKIN, PINK1) to small interfering RNA based on the CAG trinucleotide repeat expansions located in introns or untranslated regions. However, as every rule has an exception, some tumors have an increased incidence in these neurodegenerative diseases such as breast and skin cancer (melanoma). This mini-review aims to establish the epidemiology between these neurodegenerative disorders and cancer to determine the possible mechanisms involved and therefore set eventual therapeutic applications. According to our findings, we conclude the presence of an inverse relationship among most cancers and the aforementioned neurodegenerative disorders. However, this concept needs to be considered cautiously considering specific genetic and extra-genetic linkage factors for particular tumors.